Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1002/eji.200838208
|View full text |Cite
|
Sign up to set email alerts
|

Optimising anti‐tumour CD8 T‐cell responses using combinations of immunomodulatory antibodies

Abstract: Immunostimulatory mAb as vaccine adjuvants for the treatment of cancer hold considerable potential for boosting weak responses when used against immunogenic tumours, or in combination with various other vaccines. We now show that when administered with OVA, the combination of anti-4-1BB mAb with anti-CD40, anti-OX40 or anti-CD25 resulted in a fourfold enhancement in the antigen-specific T-cell response compared with anti-4-1BB mAb alone, with a similar enhancement in memory responses following rechallenge with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 49 publications
(54 reference statements)
1
28
0
Order By: Relevance
“…In these tumors antigen-specific CD8 þ immunity is downmodulated and tumors progress at a fast pace with T-cell tolerance representing the major hurdle (21). Triple combination of ISmAbs makes sense since synergistic effects of the combined treatment consisting of anti-CD137 plus anti-B7-H1 (34, 35) mAbs or anti-CD137 plus anti-OX40 mAbs (36) have been reported in mouse models of transplantable tumors. As expected from the mechanism of action of these three antibodies, we observe an increase in T-cell infiltrates in tumor tissue composed of both activated CD4 þ and CD8 þ T lymphoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…In these tumors antigen-specific CD8 þ immunity is downmodulated and tumors progress at a fast pace with T-cell tolerance representing the major hurdle (21). Triple combination of ISmAbs makes sense since synergistic effects of the combined treatment consisting of anti-CD137 plus anti-B7-H1 (34, 35) mAbs or anti-CD137 plus anti-OX40 mAbs (36) have been reported in mouse models of transplantable tumors. As expected from the mechanism of action of these three antibodies, we observe an increase in T-cell infiltrates in tumor tissue composed of both activated CD4 þ and CD8 þ T lymphoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports indicate that agonistic signaling through T cell costimulatory receptors can enhance immunity to cancer (5)(6)(7)(8)(9). Glucocorticoid-induced TNF receptor (GITR) family-related protein (10,11) is one such receptor that has received significant attention in recent years.…”
Section: Ostimulation Of T Cells Is Crucial For Generating Efficienmentioning
confidence: 99%
“…Subsequent studies by other groups and ourselves have confirmed and extended this finding that 'dual costimulation' is therapeutic in breast cancer [116], melanoma [117] and lymphoma models [118].…”
Section: Immunotherapies Overcome Tumor-induced Immunosuppressionmentioning
confidence: 70%